Linking visions feminist bioethics, human rights, and the developing world - Tong, Rosemarie 1947-; Donchin, Anne; Dodds, Susan (Rowman & Littlefield, 2004)
'Linking Visions' brings together 14 papers that engage questions about how local & global bioethical issues are made to be comparable, in the hope of redressing basic needs & demands for justice.
Keywords: Bioéthique - Droit; Feminisme; Femmes - Santé et hygiène; Féminisme - Aspect moral; Internationalisatie; Mensenrechten; Vrouwen; Éthique médicale; Feminismus; Frau; Globalisierung; Menschenrecht; aMedical ethics; aFeminism -- xMoral and ethical aspects; aBioethics; aWomen -- xHealth and hygiene; Bioethik; Aufsatzsammlung